Significantly Increased Liver Stiffness Detected by ElastPQ Ultrasound Shear Wave Elastography in Patients with Chronic Liver Disease of Over 75 Years of Age: A Cross-Sectional Study - Demirtaş, Derya; Sümbül, Hilmi Erdem (European Journal of Therapeutics, 2023)
Objective: Aging is associated with worsening of disease severity and poor prognosis in patients with non-alcoholic fatty liver disease (NAFLD), chronic hepatitis B/C (HBV/HCV), alcoholic liver disease, and liver transplantation. The aim of this study was to determine the frequency of liver fibrosis (LF) and its related parameters by calculating the liver stiffness (LS) value in patients having NAFLD and HBV/HCV who were over 75 years of age. Methods: A total of 120 individuals over 75 years of age were included in our study, according to their liver disease status as having normal liver function (NLF), NAFLD, or HBV/HCV. The LS measurement was performed with the elastography point quantification (ElastPQ) technique. If a patient had an LS value of >7.0 kPa, he or she was was accepted as having LF. Results: The LS values of patients over 75 years of age with NLF, NAFLD, and HBV/HCV were 4.75±2.34 kPa, 6.45±3.12 kPa, and 8.68±2.76 kPa, respectively. LF was found to be 25%, 40%, and 70% in the NLF, NAFLD, and HBV/HCV groups, respectively. Creatinine and AST levels were independently associated with the LS value. Creatinine, AST values, and liver size were independently determined to be associated with LF; creatinine (0.1 increase), AST (1 increase), and liver size (1 cm decrease) levels were found to increase the LF by 18.4%, 14.6%, and 42.9% respectively. Conclusion: Patients with NAFLD and HBV/HCV who were over 75 years old had their level of LS determined by liver elastography, which was increased as compared to those with NLF. Patients older than 75 years of age with NAFLD and HBV/HCV also showed significant decrease in LF as compared to NLF patient.